Response surface methodology optimization of methylene blue removal by activated carbon derived from foxtail palm tree empty fruit bunch - Farah Amni Daud; Norhisyam Ismail; Rozidaini Mohd Ghazi (Universiti Malaysia Kelantan, 2016)
The release of dyes in form of wastewater causes serious environmental problems such as retards photosynthesis, inhibit growth of aquatic biota by blocking out sunlight and utilizing dissolved oxygen. In this study, activated carbon derived from foxtail palm (Wodyetia bifurcata) empty fruit bunch (EFB) was used as an adsorbent to remove methylene blue in aqueous solution. The preparation process of activated carbon consisted of H2SO4 impregnation followed by carbonization at 300ºC for 24 hours. The optimization adsorption process was carried out using Response Surface Methodology (RSM) via Box-Behnken design. Three important operating variables namely dye concentration, contact time and adsorbent dosage were studied. The optimum conditions obtained were 100 ppm of methylene blue, 13 h of contact time and 2 g of activated carbon with the highest percentage of methylene blue removal of 99.9%. Based on the study, activated carbon derived from foxtail palm EFB showed good potential as an adsorbing agent.